A Determination of andrographolide from Andrographis paniculata growing in Thua Thien Hue with high performance liquid chromatography - Tran, Phuong Ha; Phan, Thi Diem Tran; Le, Canh Viet Cuong (Hue University Journal of Science: Natural Science, 2024)
Andrographis paniculata (Acanthaceae) is a medicinal plant commonly used in Vietnam in the 1980s. The chemical composition of the plant includes a group of diterpene lactones with antimicrobial, cytotoxic, antidiabetic, and anti-inflammatory activities. In this group, andrographolide is a typical compound. This paper describes a method for quantifying andrographolide in A. paniculata grown in Thua Thien Hue by using high-performance liquid chromatography. Andrographolide was analyzed on an RP-C18 column with a methanol/acetonitrile/water (55/10/35, v/v/v) mobile phase, a detecting wavelength of 225 nm, a flow rate of 0.5 mL/min, and an injected sample volume of 10 μL. This method displays linearity for andrographolide in the range of 200–1,000 μg/mL, and the recovery of andrographolide is 99.63 ± 0.88 %. The contents of andrographolide in root, stem, and leaf of A. paniculata grown in Vietnam were determined for the first time, and the values are 0.03 ± 0.007%, 0.57 ± 0.021%, and 3.98 ± 0.034%, respectively.